2002
DOI: 10.2320/matertrans.43.2309
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Directionally Solidified B<SUB>4</SUB>C-SiC Composites Prepared by a Floating Zone Method

Abstract: Directionally solidified B 4 C-SiC composites were prepared by a Floating Zone method. The lamellar texture was observed at 53 mol%SiC. The c-axis of B 4 C phase was tilted 20 • to the growth direction. The (102) plane and [121] direction of the B 4 C phase were parallel to the (311) plane and [121] direction of the SiC phase, respectively. The thermal conductivity of the composite parallel to the growth direction (κ ) was about twice as great as that of monolithic B 4 C. The anisotropy of electrical conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 15 publications
4
34
0
1
Order By: Relevance
“…It was reported that B 4 C-TiB 2 and B 4 C-SiC were binary eutectic systems whose eutectic compositions were 75B 4 C-25TiB 2 , 23) 80B 4 C-20TiB 2 18) and 70B 4 C-30SiC to 47B 4 C-53SiC (mol%). 10,13,24) We have found that TiB 2 -SiC was a binary eutectic system. The detailed results will be reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that B 4 C-TiB 2 and B 4 C-SiC were binary eutectic systems whose eutectic compositions were 75B 4 C-25TiB 2 , 23) 80B 4 C-20TiB 2 18) and 70B 4 C-30SiC to 47B 4 C-53SiC (mol%). 10,13,24) We have found that TiB 2 -SiC was a binary eutectic system. The detailed results will be reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…The planes perpendicular to the growth direction (growth plane) were B 4 C(104) (hexagonal), TiB 2 (100) (hexagonal) and SiC(111) (cubic, type) in the B 4 C-TiB 2 -SiC ternary eutectic composite, respectively. Binary eutectic point [13] Ternary eutectic composition TiB 2 +T Binary eutectic point [21] Binary eutectic point Figure 7 shows the indenter load dependence of Vickers micro hardness of the B 4 C-TiB 2 -SiC composites for the ternary eutectic composition (51.2B 4 C-8.1TiB 2 -40.7SiC (mol%)), and B 4 C, TiB 2 and SiC excess compositions. The hardness of B 4 C-TiB 2 -SiC composites increased with decreasing the indenter load.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some promising results have been reported for the B 4 C-SiC, B 4 C-TiB 2 and B 4 CTiB 2 -SiC eutectic composites. [18][19][20] However, the study on the TiC-TiB 2 -SiC eutectic composite has not been reported. In this study, the TiC-TiB 2 -SiC ternary composites were prepared by arc-melting, and the microstructure, hardness, thermal conductivity and electrical conductivity were investigated.…”
Section: Introductionmentioning
confidence: 99%